Investigations of variations in physical and mechanical properties of granite, sandstone, and marble after temperature and acid solution treatments - Huang, Zhen; Zeng, Wei; Gu, Qixiong; Wu, Yun; Zhong, Wen; Zhao, Kui (Construction & building materials, 2021)
•The thermodynamic properties of red sandstones were investigated up to 1000 °C.•Variation of physical properties were evaluated by the color, velocity, mass loss, porosity, and thermal conductivity.•Temperature and acidity has a considerable influence on rocks’ physical and mechanical properties. Natural rock is a very common building material, and its stability plays an important role in the safety and durability of tunnels, rock slopes, and other projects. However, tunnels and other underground projects often face the threat of disasters such as fires, and during their service, the surrounding rocks are also subject to erosion by acidic groundwater. Therefore, it is of great engineering significance to study the damage of the surrounding rocks under the threat of fire and acid groundwater. In this study, the variations in chromatic aberration, mass, P-wave velocity, porosity, thermal conductivity, and tensile strength of granite, sandstone, and marble induced by high temperature and chemical erosion are investigated from room temperature to 1000 °C. The results show that the rock materials exhibit different degrees of variation in physical and mechanical properties under the effect of high temperatures and acidic solution corrosion. Then, according to the variation of physical and mechanical properties, the formation mechanism of damage is discussed and the damage process verified by the deterioration of mechanical properties. For rocks heated to different temperatures and eroded by acid solution, the main reason for damage is the increase of cracks which destroy the structure and weaken the bonding between particles.